METHOD FOR MANUFACTURING THERMAL ISOLATION PANELS - SOERENSEN, ANSTEIN (2014)
The invention concerns a method for manufacturing thermal insulation units (1) at cryogenic temperatures with long life expectancy, including an insulation board (8) and a liquefied natural gas storage tank (10) applying the resulting units. The method comprises at least two layers of foil (2) arranged in a layer-by-layer orientation and at least one spacer (4). The following steps constitutes the manufacturing of the units: performing ultrasonic welding along the boundaries (5) of part of the layer-by-layer assembled foils, thereby forming an open envelope with at least one pocket (6), inserting the at least one spacer into at least one of the at least one pocket, the total exterior volume of the at least one spacer being smaller than the inner volume of the at least one pocket, evacuating the at least one spacer inserted pocket, and sealing the at least one spacer inserted pocket by ultrasonic welding. L'invention concerne un procédé de fabrication d'unités (1) d'isolation thermique à des températures cryogéniques, caractérisées par une longue durée de vie, comprenant une plaque (8) d'isolation, et un réservoir (10) de stockage de gaz naturel liquéfié mettant en oeuvre les unités résultantes. Le procédé fait intervenir au moins deux couches de feuille (2) agencées dans une orientation couche par couche et au moins un intercalaire (4). La fabrication des unités comporte les étapes suivantes : réaliser une soudure par ultrasons le long des frontières (5) d'une partie des feuilles assemblées couche par couche, formant ainsi une enveloppe ouverte dotée d'au moins une poche (6), insérer l'intercalaire ou les intercalaires dans la poche ou au moins une des poches, le volume extérieur total de l'intercalaire ou les intercalaires étant inférieur au volume intérieur de la ou des poches, faire le vide dans la poche où sont insérés l'intercalaire ou les intercalaires, et sceller la poche où sont insérés l'intercalaire ou les intercalaires par soudure à ultrasons.